STRATEGI PEMBELAJARAN PADA SISWA MENGALAMI KESULITAN MEMBACA - Musyarofah, Lindarty Dian; Maimun, Agus; Zuhriyah, Indah Aminatuz (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2024)
Students' limited and underdeveloped reading skills occur in students with reading difficulties, becoming the background in this study. Reading difficulties have an impact on academic and non-academic standards that have not been achieved. Something similar happened to 3 lower grade students at MI Al Latifiyah Gedogwetan Turen. This phenomenon then became the focus of research at MI AL Latifiyah Gedogwetan Turen. The purpose of the study is to describe 3 things, namely 1) the condition of students with difficulty reading at MI AlLatifiyah Gedogwetan Turen, 2) learning strategies for students with difficulty reading at MI Al Latifiyah Gedogwetan Turen and 3) implications of learning strategies on students with difficulty reading at MI Al Latifiyah Gedogwetan Turen. The research approach used is qualitative with the type of case study research. Data collection techniques are carried out by interviews, observation and documentation. Data analysis used is processing and preparing data; read the entire data; coding all data; describe data and interpret data. The results showed that 1) the condition of difficulty reading MI Al-Lathifiyah students inability to analyze letters, especially letters b, d, l, r and p, have visual memory deficiency, have not been able to understand the source of sound and lack of conceptual ability. 2) learning strategies for students with reading difficulties at MI AlLatifiyah Gedogwetan Turen are packaged in complete reading activities. In the completeness of reading used alphabetic card method, simple book text, book card and missing letter method. These four methods can complete students' reading skills, reading difficulties that are done repeatedly. 3) implications of learning strategies for students with reading difficulties in MI Al Latifiyah Gedogwetan Turen on the achievement of academic standards and non-academic standards. The academic standards achieved include knowledge, namely the achievement of an understanding of the key words of the material on the theme taught and skills in the form of body positions when reading properly and correctly. While the non-academic standards achieved include self-confidence, responsibility and social interaction.